Réponses

2014-09-20T23:59:36+02:00

A = 2 x (4 + 3) - 72/8 + 26 : 2 - 5

A = 2 x 7 - 72/8 + 26 : 2 - 5

A = 14 - 72/8 + 26 : 2 - 5

A = 14 - 9 + 26 : 2 - 5

A = 14 - 9 + 13 - 5

A = 13


B = 19 - [57 - (4 x 4 + 8)] : 3

B = 19 - [57 - (16 + 8)] : 3

B = 19 - [57 - 24] : 3

B = 19 - 33 : 3

B = 19 - 11

B = 8


A = 125 / -2 / 160 / 5

A = - 62,5 / 160 / 5

A = - 0,390625 / 5

A = - 0,078125


B = 25 + 37 / 4 / 127 + 28

B = 25 + 9,25 / 127 + 28

B = 25 + 37/508 + 28

B = 12700/508 + 37/508 + 14224/508

B = 26921/508